Authentic Leadership Influenced on the Acceptability of Information and Communication Technology for School Management - Daryanto, Daryanto; Taryudi, Taryudi; Ticoh, J D (Journal of Educational Method and Technology, 2018)
Authentic leadership and school culture are essential factors influenced the acceptability of information and communication technology (ICT) for school management. This study aims to determine the effect of authentic leadership on the acceptance of ICT for school management. This study was conducted using a casual survey with proportional random sampling technique. A total 191 respondents were agreed to join in this study. Data were analyzed using path analysis with Partial Least Square (PLS) approach. The results of this study showed that authentic leadership has a positive and significant impact on ICT acceptance. In conclusion, authentic leadership influenced directly and indirectly perceptions of ICT use, easy use, attitude to use, and actual ICT.